The Role of Pilgrimage Tourism in the Development of the National Economy - Ergashev R. Kh; Islomova D. S. (Research Parks Publishers, 2022)
The article describes the market of services in tourism as a region that creates a tourist product and creates economic relations for its buyers, and the organization and development of the market of tourism services in free tourist areas.